2014
DOI: 10.1016/j.jmbbm.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical response of human abdominal walls ex vivo: Effect of an incisional hernia and a mesh repair

Abstract: The design of meshes for the treatment of incisional hernias could benefit from better knowledge of the mechanical response of the abdominal wall and how this response is affected by the implant. The aim of this study was to characterise the mechanical behaviour of the human abdominal wall. Abdominal walls were tested ex vivo in three states: intact, after creation of a defect simulating an incisional hernia, and after reparation with a mesh implanted intraperitonally. For each state, the abdominal wall was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 22 publications
0
18
1
Order By: Relevance
“…Numerous experimental studies were conducted to characterize ex vivo the mechanical response of the abdominal wall (Junge et al, 2001;Podwojewski et al, 2013Podwojewski et al, , 2014 or its components (Ben Abdelounis et al, 2013;Cooney et al, 2015;Förstemann et al, 2011;Grässel et al, 2005;Hollinsky and Sandberg, 2007;Kirilova et al, 2011;Korenkov et al, 2001;Lyons et al, 2014;Martins et al, 2012;Rath et al, 1996;Tran et al, 2014;Wolloscheck et al, 2004). However, in vivo examinations are required to take into consideration muscle activity and to study patterns of muscle activation during different tasks and postures using electromyography (Brown and McGill, 2010;Crommert et al, 2011;McCook et al, 2009;Urquhart et al, 2005;Vera-Garcia et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experimental studies were conducted to characterize ex vivo the mechanical response of the abdominal wall (Junge et al, 2001;Podwojewski et al, 2013Podwojewski et al, , 2014 or its components (Ben Abdelounis et al, 2013;Cooney et al, 2015;Förstemann et al, 2011;Grässel et al, 2005;Hollinsky and Sandberg, 2007;Kirilova et al, 2011;Korenkov et al, 2001;Lyons et al, 2014;Martins et al, 2012;Rath et al, 1996;Tran et al, 2014;Wolloscheck et al, 2004). However, in vivo examinations are required to take into consideration muscle activity and to study patterns of muscle activation during different tasks and postures using electromyography (Brown and McGill, 2010;Crommert et al, 2011;McCook et al, 2009;Urquhart et al, 2005;Vera-Garcia et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The use of 3D image stereo correlation in combination with a physiological biomechanical simulation model to analyze strain patterns and displacement in AW research was described before [ 23 , 28 , 29 ]. However, the combination with a dynamic simulation device has not been demonstrated yet, and provides insights into the biomechanics of the sutured AW.…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, some authors (Förstemann et al, 2011;Tran et al, 2014;Podwojewski et al, 2014) found a higher compliance in the longitudinal than in the transverse directions when performing in vitro and ex vivo tests of the whole abdominal muscle samples of human. Similar results were found in Song et al (2006) with the only in vivo experiment, according to author's knowledge, performed on abdominal human tissue.…”
Section: Discussionmentioning
confidence: 99%
“…when all components are working together, are needed to better determine its mechanical behavior. Particular highlights in this regard are Podwojewski et al (2014) and Tran et al (2014), who carried out ex vivo mechanical tests on human specimens considering the contribution of the different layers, and Song et al (2006) and Szymczak et al (2012), who performed in vivo tests measuring on a live human abdomen while this was subjected to different stresses. All these works, however, have some differences or limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation